Genetic correlation between amyotrophic lateral sclerosis and schizophrenia - McLaughlin, Russell L.; Schijven, Dick; Van Rheenen, Wouter; van Eijk, Kristel R.; O'Brien, Margaret; Kahn, René S.; Ophoff, Roel André; Goris, An; Bradley, Daniel G.; Al-Chalabi, Ammar; van den Berg, Leonard H.; Luykx, Jurjen J.; et al. (Nature Communications, 2017)
We have previously shown higher-than-expected rates of schizophrenia in relatives of patients with amyotrophic lateral sclerosis (ALS), suggesting an aetiological relationship between the diseases. Here, we investigate the genetic relationship between ALS and schizophrenia using genome-wide association study data from over 100,000 unique individuals. Using linkage disequilibrium score regression, we estimate the genetic correlation between ALS and schizophrenia to be 14.3% (7.05-21.6; P=1 × 10−4) with schizophrenia polygenic risk scores explaining up to 0.12% of the variance in ALS (P=8.4 × 10−7). A modest increase in comorbidity of ALS and schizophrenia is expected given these findings (odds ratio 1.08-1.26) but this would require very large studies to observe epidemiologically. We identify five potential novel ALS-associated loci using conditional false discovery rate analysis. It is likely that shared neurobiological mechanisms between these two disorders will engender novel hypotheses in future preclinical and clinical studies.
Project MinE GWAS Consortium: Aleksey Shatunov, Jochen H. Weishaupt [und viele weitere]
Gesehen am 08.07.2021